MONNA, a Potent and Selective Blocker for Transmembrane Protein with Unknown Function 16/Anoctamin-1 - Oh, Soo-Jin; Hwang, Seok Jin; Jung, Jonghoon; Yu, Kuai; Kim, Jeongyeon; Choi, Jung Yoon; Hartzell, H. Criss; Roh, Eun Joo; Lee, C. Justin (AMER SOC PHARMACOLOGY EXPERIMENTAL THERAPEUTICS, 2013)
Transmembrane protein with unknown function 16/anoctamin-1 (ANO1) is a protein widely expressed in mammalian tissues, and it has the properties of the classic calcium-activated chloride channel (CaCC). This protein has been implicated in numerous major physiological functions. However, the lack of effective and selective blockers has hindered a detailed study of the physiological functions of this channel. In this study, we have developed a potent and selective blocker for endogenous ANO1 in Xenopus laevis oocytes (xANO1) using a drug screening method we previously established (Oh et al., 2008). We have synthesized a number of anthranilic acid derivatives and have determined the correlation between biological activity and the nature and position of substituents in these derived compounds. A structure-activity relationship revealed novel chemical classes of xANO1 blockers. The derivatives contain a -NO2 group on position 5 of a naphthyl group-substituted anthranilic acid, and they fully blocked xANO1 chloride currents with an IC50<10 mM. The most potent blocker, N-((4-methoxy)-2-naphthyl)-5-nitroanthranilic acid (MONNA), had an IC50 of 0.08 mu M for xANO1. Selectivity tests revealed that other chloride channels such as bestrophin-1, chloride channel protein 2, and cystic fibrosis transmembrane conductance regulator were not appreciably blocked by 10 similar to 30 mu M MONNA. The potent and selective blockers for ANO1 identified here should permit pharmacological dissection of ANO1/CaCC function and serve as potential candidates for drug therapy of related diseases such as hypertension, cystic fibrosis, bronchitis, asthma, and hyperalgesia.
Keywords: ACTIVATED CHLORIDE CHANNEL; CA2+-ACTIVATED CL; K+ CHANNELS; TMEM16A; EXPRESSION; SECRETION; NEURONS